A dual bevel compact planar monopole antenna for UHF application - Muzammil, Jusoh; Mohd Faizal, Jamlos, Dr.; Muhammad Ramlee, Kamarudin; Zahari, Awang Ahmad; Muhamad Asmi, Romli; Naseer, Sabri (The Electromagnetics Academy, 2012)
Link to publisher's homepage at http://emacademy.org/